Transplantasi Organ Tubuh Menurut Perspektif Hukum Islam - Yusriadi, Yusriadi; Zulhamdi, Zulhamdi (Syarah: Jurnal Hukum Islam dan Ekonomi, 2022)
The Qur'an does not mention transplantation explicitly as specifically, but there are several verses of the Qur'an that contain a discussion of transplantation in general, as mentioned in (QS. 2: 2), (QS. 2 : 195), (Qur'an 5: 2), (QS. 59: 9), (QS. 17: 70), (QS. 5: 32). The research technique here uses the library research method, which is done by searching for research data or information through reading scientific journals, reference books and publication materials available in the library. The majority of fiqh scholars consisting of some Hanfiyyah scholars, some Malikiyyah scholars, Syfi'iyah scholars, some Syfi'iyah scholars, Hanbali scholars and Zaidiyah scholars, are of the opinion that using human organs as treatment is permissible in a state of arȗrat. It is required that there must be permission from the heirs who can be considered and their abilities with the will of a person who has died. According to Jumhur ulama, it is permissible to transplant, with the concrete reason that all rights of a corpse when it is still alive become the right of the owner to inherit the organs of the body before he dies. From the International Fatwa Council, it is permissible to transplant human vital organs, and cannot be traded.